DETERMINING THE IMPORTANCE OF GLYCEMIC VARIABILITY IN GESTATIONAL DIABETES MELLITUS USING VARIOUS TECHNIQUES - Nida Öztop; Ayşe Kubat Üzüm; Selda Çelik; Cemile İdiz; Yıldız Tütüncü; Elif Bağdemir; Nevin Dinççağ (İstanbul Tıp Fakültesi Dergisi)
Objective: The study aims to determine glycemic variation in patients with GDM and to evaluate the effect on the fetal growth using a continuous glucose monitoring system (CGMS) and to investigate the correlation between glucose variation through biomarkers including HbA1c, fructosamine (FRM), and 1.5-Anhydroglucitol (1.5-AG). Materials and Methods: The study involves 31 women with GDM at gestational week ≥35 who’d only had diet therapy. Blood glucose levels were monitored for three consecutive days using CGMS to evaluate mean blood glucose levels and mean absolute difference (MAD). Self-monitoring of blood glucose (SMBG) was required from the patients while having the CMGS on their body. Blood samples were collected to measure serum 1.5-AG, HbA1c, and FRM. Results: The mean levels were HbA1c=5.0±0.3%, FRM=2.1±0.2 μmol/L, 1.5-AG=17.0±4.9 ng/ml, and 3-day average max-min glucose range=131.1±22.5 and 54.7±11.6 mg/dl (MAD=6.7±3.1%). The mean glucose levels measured using SMBG and CGMS were similar (82.9±10.2 vs 86.1±10.3 mg/dL). No correlation occurred between CMGS and biomarkers. The baby weight at birth and head circumference was determined to be lower for patients with glucose fluctuations. Conclusion: Biomarkers do not reflect glycemic fluctuation, and regular SMBG is required to achieve the desired glucose level, even in diet-regulated GDM. Lower head circumference and birth weight were determined in GDM mothers with high glycemic fluctuations, and CGMS may be an alternative method despite its cost and application difficulties.